PERSPECTIVES ON SOCIAL PEDAGOGY IN BRAZIL: EDUCATION, INCLUSION, AND SOCIAL TRANSFORMATION - Mazeto, Jhiones de Arruda; de Moraes, Francelina Fontenelle; de Jesus, Camila Aparecida Miranda; Rodrigues, Jozivane Ferreira Silva; Martins, Elkslene Ramos; Martines, Renata Galvani Garcia; Ribeiro, Creuza Rosa; de Lima, Lorrayni Cristina Arruda; Chaves, Rosanilda Meira (Seven Editora, 2026)
Social Pedagogy has established itself as a relevant field in the Brazilian educational landscape, especially regarding the promotion of social inclusion and the guarantee of rights. This article aims to analyze the perspectives of Social Pedagogy in Brazil, highlighting its role in non-formal educational contexts and its contribution to civic education. The research, with a qualitative and bibliographical approach, is based on authors who discuss education as a social and emancipatory practice. It is evident that Social Pedagogy expands educational spaces, working with vulnerable populations and promoting meaningful learning processes. It concludes that this area represents an important strategy for building a more just, democratic, and inclusive society.